Bibliometric study on the variables solar energy, economy, Brazil - Ítalo Freire, Anderson; Fontgalland, Isabel (Latin American Journal of Energy Research, 2023)
This bibliometric study traces and refines the condition of publications related to Solar Energy, Economy, and Brazil as joint terms in the same publication, varying from the year 2010 to the year 2020, considering the appearance of the term in topics, titles, or abstracts, identifying the number of these publications, their respective authors, in addition to the most cited documents and the most used keywords in scientific articles. Bibliometric studies are tools that greatly help the analysis of scientific production in each area, and it is no different in topics related to the economy and the electricity sector, a sector that has grown in recent years here in Brazil and in the world. Having this initial aspect as a basis for justification and noting that this growth tends to encourage publications within the area under analysis, this article is divided into 4 parts, the first and second relating to the introductory part and the methodology used in the investigation, and the last two parts related to what was essentially analyzed within the scope of the work and the conclusion on how these publications were stand out in academia and how production in the area can be improved based on this investigation.